2009
DOI: 10.3174/ajnr.a1890
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Transverse Sinus Stenting of Patients with Idiopathic Intracranial Hypertension

Abstract: BACKGROUND AND PURPOSE:The pathophysiology of IIH remains unknown. TS stenoses have been observed in a high proportion of these patients. Stent placement to remove this potential obstruction to venous outflow has been proposed as a treatment option for patients with IIH refractory to medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
91
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(99 citation statements)
references
References 52 publications
3
91
0
5
Order By: Relevance
“…Donnet et al 23 reported 10 patients with IIH, stented without complication; 6 were cured and 4 improved. Bussiere et al 24 reported 10 patients with IIH stented, with resolution of venous hypertension in all and symptom improvement in most.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Donnet et al 23 reported 10 patients with IIH, stented without complication; 6 were cured and 4 improved. Bussiere et al 24 reported 10 patients with IIH stented, with resolution of venous hypertension in all and symptom improvement in most.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] In the past 9 years, we have stented 1 transverse sinus in 52 patients with IIH with transverse sinus stenosis who either failed medical treatment or had fulminant visual loss. We reviewed the data; on the basis of a mathematic model 25 that incorporates a collapsible transverse sinus as a Starling-like resistor (one in which the resistance is a linear function of pressure external to the resistor lumen), we attempted to reconcile opposing views of transverse sinus stenosis as a cause and a consequence of intracranial hypertension.…”
mentioning
confidence: 99%
“…13,19,22 In a recent review, a group of Canadian researchers reviewed 8 studies and analyzed a total of 40 patients treated using the method. 26 After stenting, 82.5% of the patients showed resolution or significant improvement of their headaches, and 91% of individuals exhibiting papilledema upon admission showed an improvement of this sign. 26 Akin to the present investigation, headache ipsilateral to the stent occurred, an event observed in over 50% of the patients, and characterized as transient in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…26 After stenting, 82.5% of the patients showed resolution or significant improvement of their headaches, and 91% of individuals exhibiting papilledema upon admission showed an improvement of this sign. 26 Akin to the present investigation, headache ipsilateral to the stent occurred, an event observed in over 50% of the patients, and characterized as transient in most cases. Ahmed et al attributed this symptom to the distension of the transverse sinus after the procedure, and it generally improved after one week.…”
Section: Discussionmentioning
confidence: 99%
“…I humbly concede that our meta-analysis of the dural venous sinus stent (DVSS) is not significantly different from the previously published meta-analysis on the topic of DVSS for idiopathic intracranial hypertension (IIH), 2 though another meta-analysis on DVSS was not the goal of the article. The DVSS portion of the article represented only one-third of the focus of the article.…”
mentioning
confidence: 88%